Health professionals’ views and experiences of breaking bad news in the Eastern Mediterranean Region: a scoping review - Yousuf, Abdulla Ahmad A. A.; Stewart, Derek Charles; Kane, Tanya; Soltani, Abderrezzaq; Al-Khal, Abdullatif; Sethi, Ahsan (Frontiers in Medicine, 2024)
Breaking bad news is a critical yet challenging aspect of healthcare that requires effective communication skills, empathy, and cultural sensitivity. Health professionals in the World Health Organization's (WHO) Eastern Mediterranean Region face unique cultural and social factors distinct from other parts of the world. This scoping review aims to comprehensively explore the peer-reviewed literature on the health professionals' experiences in delivering bad news within the WHO's Eastern Mediterranean Region.This scoping review was conducted according to the Joanna Brigg Institute's scoping review methodology and reported utilizing the Preferred Reporting Items for Systematic Reviews extension for scoping review (PRISMA-ScR) guidelines. A search using a combination of keywords and MeSH terms related to 'breaking bad news' and 'health professionals' was performed in PubMed, Scopus, CINAHL, EBSCO, ERIC via Embase, and Dar Almandumah (Arabic) databases. Common themes were synthesized from studies conducted in the WHO's Eastern Mediterranean Region.Out of 4,883 studies initially identified in the databases, 24 studies met the inclusion criteria, involving a total of 4,710 participants, including physicians, nurses, and residents. The studies were published between 2006 and 2022, predominantly from Iran (n = 12). The majority employed a cross-sectional design (n = 21) or mixed methods (n = 3), with a notable absence of qualitative studies. No studies used theoretical frameworks. More than half of the studies (n = 14) reported that participants had positive attitudes toward breaking bad news. This positivity was evident in their willingness to share bad news, perceived possession of adequate knowledge, positive attitudes, having received training, awareness of accepted approaches, and adherence to protocols. The lack of training and limited awareness of established protocols like SPIKES, ABCDE, and BREAKS for breaking bad news were major concerns among participants.The scoping review reveals both positive and negative experiences of breaking bad news by health professionals in the WHO's Eastern Mediterranean Region. Most studies highlight the need for culturally sensitive targeted education and training programs on breaking bad news. Further research, particularly using qualitative methodologies and theoretical frameworks is warranted.